2017
DOI: 10.1071/rd16190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freezing and activation on membrane quality and DNA damage in Xenopus tropicalis and Xenopus laevis spermatozoa

Abstract: Abstract. There is growing concern over the effect of sperm cryopreservation on DNA integrity and the subsequent development of offspring generated from this cryopreserved material. In the present study, membrane integrity and DNA stability of Xenopus laevis and Xenopus tropicalis spermatozoa were evaluated in response to cryopreservation with or without activation, a process that happens upon exposure to water to spermatozoa of some aquatic species. A dye exclusion assay revealed that sperm plasma membrane in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…activated sperm), suggests that X. laevis sperm retain the capability to fertilise under optimal conditions even when they have significant plasma membrane and DNA damage [44]. The lack of an effect of activation on the state of frozen-thawed sperm is in agreement with Morrow et al.…”
Section: Discussionsupporting
confidence: 85%
“…activated sperm), suggests that X. laevis sperm retain the capability to fertilise under optimal conditions even when they have significant plasma membrane and DNA damage [44]. The lack of an effect of activation on the state of frozen-thawed sperm is in agreement with Morrow et al.…”
Section: Discussionsupporting
confidence: 85%
“…Sperm can be used immediately or stored for extended period of time either at −80 °C or in liquid nitrogen. In general, fertilization from cryopreserved sperm is efficient and animals generated develop normally, however, it has also been demonstrated that cryopreserving sperm does cause some plasma membrane damage and DNA fragmentation in the spermatozoa [7, 8]. …”
Section: Methodsmentioning
confidence: 99%
“…The sperm of Cryptobranchus proved amenable to cryopreservation with the slow lowering of straws into a LN2 vapour (Dale McGinnity personal communication), but using a similar freezing method with Andrias only recovered <10% motility [47]. In fish optimal cooling rates are membrane lipid dependent [114,115] and this is expected to be the case with amphibian sperm.…”
Section: Cooling Rates and Cryopreservationmentioning
confidence: 99%
“…Many morphological deformations can be found in post-thaw amphibian spermatozoa, such as swelling or rupture of the plasma membrane, loss of the nuclear envelope, fracture of the perforatorium and axoneme, degeneration of the undulating membrane and disappearance of the mitochondrial ridge [48,115]. Morphological damage may be associated with impacts on post-thaw activation mechanisms where fish [116,117] or Anuran [53,112] spermatozoa are intact but unable to activate.…”
Section: Morphological Integrity Of Spermmentioning
confidence: 99%